ANALISIS PENGARUH LOKASI, KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DI T.B RAJAWALI KALICILIK, DEMAK (studi pada Toko Bangunan Rajawali Kalicilik, Demak) - Raharjo, Korniawan; Santosa, Suryono Budi (Diponegoro Journal of Management, 2015)
Various consumers’ needs create different buying motives, so do the quantity. To understand the needs and tastes of consumers, a company should discern its consumers’ behavior. The consumer buying behavior also applies in the decision regarding the purchase of building materials. Along with the increasing number of stores selling building supplies, stores should pay  more attention to consumer behavior.The purpose of the research is to analyze the effects of location, service quality and perceptions of price on consumers’ buying decision. Populations in this research are consumers buying at TB Rajawali Demak, with the total sample of 100 respondents. The sample collection technique used is accidental sampling. The type of data used is primary data using questionnaire and secondary data using related literature. Data analyses tool used is multiple regression.Result of this research indicates that location service quality and perceptions of price positively correlated to consumers’ buying decision. The more strategic a location, the better service quality and the more affordable price, therefore increase the buying decision.